Synthesis, characterization and influence of fuel to oxidizer ratio on the properties of spinel ferrite (MFe2O4, M = Co and Ni) prepared by solution combustion method. Issue 17 (1st December 2017) - Sudheesh, V.D.; Thomas, Nygil; Roona, N.; Baghya, P.K.; Sebastian, Varkey
Abstract: The effect of fuel to oxidizer ratio on the crystallite size and the physical properties of cobalt and nickel ferrite samples synthesized by solution combustion method using glycine as fuel are reported. Powder X-ray diffraction studies indicate that pure nanocrystalline ferrite phase is formed when the fuel to oxidizer ratio is less than one. The crystallite size can also be controlled by controlling the fuel to oxidizer ratio. The Mössbauer and Raman studies on the sample prepared at F/O 0.6 indicate that high quality samples having inverse or mixed spinel structure can be prepared by solution combustion method. Room temperature magnetization curves of the samples prepared under fuel lean condition have a systematic trend of coercivity with increasing crystallite size.